2015
DOI: 10.1021/acs.organomet.5b00684
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of Manganese(II) Complexes Containing N-Heterocyclic Carbene Ligands

Abstract: A series of manganese(II) complexes containing arylsubstituted N-heterocyclic carbene (NHC) ligands have been synthesized and characterized. Chloride complexes of Mn(II) containing the NHC ligands 1,3-bis(2,6-diisopropylphenyl)imidazol-2-ylidene (IPr) and 1,3dimesitylimidazol-2-ylidene (IMes) were prepared in straightforward fashion by direct carbene addition to MnCl 2 (THF) 1.6 . These complexes exist as chloride-bridged dimers in solution of formula [Mn 2 Cl 2 (μ-Cl) 2 (NHC) 2 ]. The monomeric complex [MnCl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 86 publications
2
7
0
Order By: Relevance
“…In all complexes, the Mn II centers are in a distorted tetrahedral coordination environment. The geometric situation is similar to those observed in the NHC‐Mn II complexes [MnCl 2 (C{N( i Pr)C(Me)} 2 ) 2 ] and [MnCl 2 (IMes) 2 ] (IMes=1,3‐dimesitylimidazol‐2‐ylidene) . However, akin to the situation in Fe II and Ge II complexes stabilized by L1 , the pyridine N atom in [L1]MnCl 2 is reluctant in coordinating to the Mn atom as indicated by the relatively long Mn(1)–N(1) distance of 3.259 Å.…”
Section: Methodssupporting
confidence: 60%
See 1 more Smart Citation
“…In all complexes, the Mn II centers are in a distorted tetrahedral coordination environment. The geometric situation is similar to those observed in the NHC‐Mn II complexes [MnCl 2 (C{N( i Pr)C(Me)} 2 ) 2 ] and [MnCl 2 (IMes) 2 ] (IMes=1,3‐dimesitylimidazol‐2‐ylidene) . However, akin to the situation in Fe II and Ge II complexes stabilized by L1 , the pyridine N atom in [L1]MnCl 2 is reluctant in coordinating to the Mn atom as indicated by the relatively long Mn(1)–N(1) distance of 3.259 Å.…”
Section: Methodssupporting
confidence: 60%
“…The geometrics ituationi ss imilar to those observed in the NHC-Mn II complexes [MnCl 2 (C{N(iPr)C(Me)} 2 ) 2 ] [12] and [MnCl 2 (IMes) 2 ]( IMes = 1,3-dimesitylimidazol-2-ylidene). [13] However, akin to the situation in Fe II and Ge II complexes stabilized by L1, [2f, 14] the pyridine Na tom in [L1]MnCl 2 is reluctant in coordinating to the Mn atom as indicatedb yt he relativelyl ong Mn(1)-N(1) distance of 3.259 . This is in contrast to PNP pincer-type Mn II complexes with much shorter N(py)-Mn distances, [9d, 15] which can be rationalized by the stronger s-donors trengtho fS i II versus P III towards Mn.…”
mentioning
confidence: 99%
“…177 Solid-state magnetic susceptibility studies revealed a high spin state of 5/2, which corrects the previous analyses that claimed an intermediate spin of 3/2 (attributed to impurities or partial decomposition of the compound). 178 Reaction of MnCl2 in THF with free NHC affords the chloride-bridged dimer 179,180 These compounds are precursors to dimeric alkyl compounds dimeric alkyl compounds such as 172. Compound 172 may react with Si(OEt)4 to selectively form MeSi(OEt)3.…”
Section: B) Molybdenum and Tungstenmentioning
confidence: 99%
“…More recently, Tonzetich and co-workers reported a series of manganese(II) complexes (Fig. 16) [64] that can be used as precursors for alkyl and aryl complexes. They also tested the dimeric complex in CAC cross-coupling, but with disappointing results.…”
Section: Nhc Complexesmentioning
confidence: 99%
“…A few years later, Tonzetich and coworkers reported the synthesis of the alkyl complex [Mn(IPr)(CH 2 -SiMe 3 ) 2 ] from the corresponding Cl-bridged dimer complex (Fig. 16) [64].…”
Section: Alkyl and Aryl Complexesmentioning
confidence: 99%